Human milk oligosaccharides produced by synthetic biology - Jessica Bensimon; Xiaonan Lu (Journal of Agriculture and Food Research)
The benefits of human breast milk (HBM) to newborn growth, development, and overall health have been well investigated. As breastfeeding rate has declined significantly, the use of infant formula has risen and remains a significant component of the infant's diet. HBM contains several essential nutritional components, with human milk oligosaccharides (HMO) being the third most abundant following lactose and lipids. A diverse array of HMOs is known to exert great benefits in intestinal, immune, and cognitive functions. In contrast to HBM, infant formula containing mainly bovine milk lacks the diversity of HMOs. Efforts have been made to replicate this characteristic in infant formula through chemical and chemoenzymatic synthesis as well as microbial production. Utilizing microbial hosts appears to be more favourable due to its accessibility and cost-efficiency. Escherichia coli has been preferably used due to its high incorporation of DNA, high-level expression capability, and rapid growth. However, potential endotoxin contamination raises health concerns and prevents approval as Generally Recognized as Safe (GRAS) by the FDA. This prompts the use of other microbes such as Bacillus subtilis. Future research in this area is needed to optimize effective procedures using microbial hosts, high yield production, and economic feasibility. This may lead to infant formulas closely mimicking HBM and its health benefits.